Knowledge and Skills Used and the Satisfaction Derived in the Choice of Apparel among University Students - Mugalavai, Violet K; Mugenda, Olive; Mburugu, Keren (Nurture, 2009)
The purpose was to examine the relationship between the knowledge and skills used in the selection of apparel and the satisfaction obtained. Data were collected from 210 undergraduate students of which 94 were females and 116 were males. A self administered questionnaire and focus group discussions were used. Knowledge and skills related to apparel choice were measured by a 12- item Likert scale. Satisfaction was measured using a 15- item test asking how the respondents personally feel about their clothes and what others think about them. Level of satisfaction was higher among those who had adequate knowledge. Female respondents scored higher than the male respondents on most of the attributes tested and depicted cognizance in the use of knowledge and skills. Level of satisfaction was high, with gender and year of study being significant determinants.